ANALISIS KUALITAS AIR PADA SALURAN IRIGASI UNTUK KEBUTUHAN PADI SAWAH DI DESA SUNGAI RADAK I KECAMATAN TERENTANG KABUPATEN KUBU RAYA - Fitriadi, Ferra; junaidi, Junaidi (Jurnal Sains Pertanian Equator, 2016)
The research aimed to know the quality of water irrigation for paddy soil"™ needs in Sungai Radak I, Terentang District, Kubu Raya Regency. The samples were conducted and observed in the field and the water was conducted in laboratory. The direct observation involved water temperature, brightness, water pH, and water discharge. The analisis conducted in laboratory observed electrical conductivity (EC), boron, alkalinity, Sodium Adsorption Ratio (SAR), Residual Sodium Carbonate (RSC), Field research was conducted to observe and take water samples in a waterway gate point which flows to the first irrigation during tidal. According to the observation in the field it showed that the average score for water quality at high tide was water temperature 28,4oC, brightness 22,6 cm, water pH 6,83, water discharge 0,391 m3/second while at low tide was water temperature 28,7oC, brightness 26,6 cm, water pH 6,61, water discharge 0,075 m3/second. Based on laboratory result it showed that the average of water quality at high the was EC 0,017 dS/m, boron 0,004 mg/l, alkalinity 1,66 mg/l, SAR 0,6543, RSC -0,1603 meq/l while at low tide was EC 0,021 dS/m, boron 0,006 mg/l, alkalinity 2,83 mg/l, SAR 0,8001, RSC -0,1368 meq/l, base on these result the research findings showed that water quality at tidal in Sungai Radak I, Terentang District, Kubu Raya Regency was appropriate for irrigation. Key words: Water Quality, Irrigation Channel, Paddy Soil.